Impact of Mass Electric Mobility on the Power Distribution Network: Case Study of San Andrés Island, Colombia - Ramirez Acero, Julio Cesar; Isaza Ruget, Ricardo; Rosero Garcia, Javier (International Review on Modeling and Simulations, 2025)
This work evaluates the impact of massive electric mobility on the electrical distribution network, by using the distribution circuit of San Andrés Island as a case study. Through various simulation methods, scenarios of operation and mass adoption of electric vehicles are analyzed, considering both uncontrolled and controlled charging. Three key premises are highlighted regarding demand management, its influence on network reliability indicators, and the proposal of a methodology for the design and planning of distribution networks with high penetration of electric vehicles. The importance of the relationship between the installed power of the user and the load of the electric vehicle, as well as the identification of new design factors, is emphasized. Finally, the need to design and build modular and interoperable distribution networks that can adapt to the increasing penetration of massive electric mobility, and to implement advanced metering technologies to monitor demand status and adjust design models, is stressed.